ANALISIS PENGGUNAAN APLIKASI PENGOLAH NILAI RAPORT DALAM MENINGKATAN KEMAMPUAN TEKNOLOGI GURU DI PKPPS AL HIDAYAH KARANGSUCI - Ibnu Abinnashih; Alief Budiyono (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This study aims to analyze the use of report card processing applications in improving the technological abilities of teachers at PKPPS Al Hidayah Karangsuci. The research method used is a case study approach using a qualitative approach. The time for the research was carried out for one month, from February 1 to March 1 2023. The research subjects consisted of school principals, curriculum representatives, and homeroom teachers. Data collection techniques namely interviews, observation, and documentation. The results of this study indicate that the use of a report card processing application has the potential to provide convenience and efficiency in managing report card grades. Teachers can reduce the time needed to calculate and process data manually by using this application. However, weaknesses were also found in terms of lack of facilities and infrastructure which could affect the teacher's enthusiasm in learning and understanding grade processing applications.